Teachers'and students' code switching in the ESL classroom / Masliza Mat Zali - Mat Zali, Masliza (2012)
In English Second Language (ESL) classroom, the use of First Language (LI) is prohibited as learning in the target language will help students to master the language.In dealing with low proficiently students, the exposure might be different. However, in order toprevent these students using LI, the use of code switching is a strategy to allow teachers to give comprehensible input to students in the class. The main purpose of this study is to identify the languages used by teachers and students in communicating in the ESL classroom and to capture the characteristics of code switching in their discourse. The study aims to identify the types, functions and the reasons for code switching in Standard Four classrooms. The data of this atudy were obtained from two sources; (1) audio recordings of English Lesson and (2) interviews were conducted with the informants. The classes of three teachers with 20 students from each class were selected for observation and were also chosen as subjects. Data was then categorized according to types, functions and the reasons for code switching.The teachers and students used two languages; English and Malay. The finding shows that most students used inter-sentential switching but teachers frequently used intrasentential switching in their interactions. Teachers mostly used code switching to reiterate, emphasize and clarify the sentence and code switching was used effectively in teachers and students interaction. However, it would be more interesting if a bigger sample to study the patterns of code switching is being examined among higher learning institution students as to provide wider views on why code switching exists and its extent.